2020
DOI: 10.21315/mjms2020.27.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Brief Psychological Interventions for COVID-19 Pandemic: Introduction of a Locally-Adapted Brief Intervention for Mental Health and Psychosocial Support Service

Abstract: The ultra-brief psychological interventions (UBPI) was created in 2018 to empower healthcare providers with psychological skills that can be delivered within a short period. Techniques used within UBPI were adopted from a variety of well established psychotherapies and distilled into its core essentials. This enabled practitioners of UBPI to deliver specific psychological skills in the appropriate context to the client within a period of 15–20 min. UBPI was also manualised to standardised training of practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 6 publications
0
26
1
Order By: Relevance
“…ventilators) will help relieve the stress of having to treat people with infections, and improve their mental wellbeing. During this COVID-19 crisis, various interventions were offered to healthcare workers, such as a peer-supported resilience intervention in the USA (Albott et al, 2020), e-package with Agile methodology in the UK (Blake, Bermingham, Johnson, & Tabner, 2020), and the ultra-brief psychological intervention in Malaysia (Ping et al, 2020). The e-package in the UK included evidence-based guidance, support, and signposting relating to psychological wellbeing, and results of this pre-post intervention ( n = 55) revealed that 82% of healthcare participants used the information in their work or home lives (Blake et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ventilators) will help relieve the stress of having to treat people with infections, and improve their mental wellbeing. During this COVID-19 crisis, various interventions were offered to healthcare workers, such as a peer-supported resilience intervention in the USA (Albott et al, 2020), e-package with Agile methodology in the UK (Blake, Bermingham, Johnson, & Tabner, 2020), and the ultra-brief psychological intervention in Malaysia (Ping et al, 2020). The e-package in the UK included evidence-based guidance, support, and signposting relating to psychological wellbeing, and results of this pre-post intervention ( n = 55) revealed that 82% of healthcare participants used the information in their work or home lives (Blake et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The e-package in the UK included evidence-based guidance, support, and signposting relating to psychological wellbeing, and results of this pre-post intervention ( n = 55) revealed that 82% of healthcare participants used the information in their work or home lives (Blake et al, 2020). Feedback from healthcare workers suggests that qualitative wellness is improved by providing a free online resource manual targeting psychological skills and interventions to reduce the distress caused by uncertainty during the pandemic (Ping et al, 2020). Many countries have developed dedicated teams to provide mental health support for healthcare workers; however, the type of support needed depends on the stage of the pandemic, and can benefit from peer and professional counseling (Isaksson Rø, Veggeland, & Aasland, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for depression, anxiety, and stress, both psychological factors contribute significantly to the total variance in all three scores, whereas psychological mindedness does not have a similar contribution. This suggests that it is crucial that we perform interventions that are able to increase mindfulness and psychological flexibility, especially in frontline workers, be it in healthcare or nonhealthcare settings [65]. One of the interventions that can be considered is the ultra-brief psychological intervention (UBPI).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is crucial that early preventative measures at the university level be undertaken to increase surveillance at the alert phase (26,27), especially taking into account the impact of digital learning on student burnout and mental health (28). Crucially, brief psychological interventions also need to be undertaken to reduce psychological morbidity, especially in rural areas (29,30). Digital interventions can also be employed to expedite monitoring of quarantine and streamline surveillance to reduce unnecessary healthcare worker man-hours (31).…”
Section: Discussionmentioning
confidence: 99%